Cloud Computing Vis-à-Vis Agricultural Development towards Digital and Smarter Agricultural Informatics Practice - Paul, P. K.; Sinha, R. R.; Aithal, P. S.; Saavedra, Ricardo; Aremu, Bashiru; Mewada, S. (Asian Journal of Engineering and Applied Technology, 2020)
Cloud computing is an emerging and technologies within the Information Technology field and also technological era. Cloud Computing is used in almost all sectors, fields, organizations and institutions; where Information Technology is used. Cloud computing deals with the delivery of computing infrastructure, application and many need based collaboration viz. hardware, software, networks, storage, interfaces as a service by the internet and similar systems. Cloud Computing is also known as virtualization technology as it supports from the remote places depending upon the needs of the users and from the centralized unit and systems. It also allows healthy computing services including storage, memory, processing with many advantages and facilities with several platforms; hence it is become widely recognized around the world. Most importantly also offers many add on facilities with low cost implementation for the infrastructure. Cloud Computing enables payment depending upon the need of the organization, client and institutions, and facilities offered. It also acts as virtual hardware and also provides elasticity, network based services. Among the stakeholders of Cloud Computing; the most important are growing is Agriculture Sectors. It is useful in pre production and post production of the agricultural systems. This paper talks about the basics of Cloud computing including current and future applications in agriculture and allied domains. Paper also deals with the issues, challenges of Cloud computing in agro and allied domain in brief. Paper also suggested few concerns on Cloud Computing application in smarter agriculture dealing and Agriculture Informatics is also been provided, herewith.